Evaluating Strategic Options Using QSPM: Enhancing Plaza Indonesia Realty's Competitive Edge - Christiadi, Henry; Alamsyah, Muhammad Iqbal (International Journal of Indonesian Business Review, 2024)
This research explores how Plaza Indonesia Mall aligns its corporate and business strategies in response to challenges like heightened competition, digital advancements, and sustainability requirements. Utilizing a quantitative descriptive methodology, the study relies on secondary data from financial documents, industry reports, and scholarly literature. A SWOT analysis is conducted to assess the mall's internal strengths and weaknesses alongside external opportunities and threats. Subsequently, the Quantitative Strategic Planning Matrix (QSPM) is used to evaluate and prioritize strategic alternatives based on their appeal and feasibility. The QSPM analysis reveals that the digitalization strategy is the most attractive, scoring the highest Total Attractiveness Score (TAS) of 2.83, highlighting the need for enhancing PLIN's digital presence, integrating e-commerce, and leveraging digital marketing to adapt to evolving consumer behaviors. The differentiation strategy, which emphasizes capitalizing on PLIN's prime location and strong brand reputation, also ranks highly with a TAS of 2.81, reinforcing the importance of providing a premium customer experience and differentiating offerings to maintain competitive advantage. Although the Cost Efficiency Strategy scored the lowest TAS of 2.76, it remains vital for operational efficiency and profitability. The findings suggest that a balanced approach prioritizing digitalization, differentiation, and cost efficiency will enable PLIN to effectively navigate market challenges, capitalize on growth opportunities, and sustain long-term success. This study provides strategic insights for PLIN and other property firms seeking to enhance their competitive positioning through targeted strategic initiatives.